IDENTIFICACIÓN, EN LAS COMPETENCIAS DE LA TEORÍA DE LA MENTE, DE LA INFLUENCIA DEL COCIENTE INTELECTUAL EN UN GRUPO DE ESQUIZOFRÉNICOS - PAZ LOPEZ HERRERO (Análisis y Modificación de Conducta, 2013)
Schizophrenia sufferers may have Theory of Mind (ToM) deficits. These deficits are not as severe as those shown by people with other disorders such as autism, because schizophrenic patients can solve simple ToM tests using their Intelligence Quotient (IQ) and general problem-solving skills. Our aim was to study ToM by asking a group of schizophrenics to perform a mental verbs task. We then identified the categories into which the mental verbs were grouped and their use profile, and assessed the influence of intelligence quotient. We observed that those with a higher IQ had lower ToM deficits. Subjects with average IQs grouped the mental activities quite well and those with low IQ performed the task poorly as a result of the combined effects of schizophrenia processes and low IQ.